2019
DOI: 10.1038/s41388-019-0932-1
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-reprogrammed tricarboxylic acid cycle promotes the growth of human breast tumorigenic cells

Abstract: Clinical applications of antiangiogenic agents profoundly affect tumor cell behaviors via the resultant hypoxia. To date, how the hypoxia regulates tumor cells remains unclear. Here, we show that hypoxia promotes the growth of human breast tumorigenic cells that repopulate tumors [tumor-repopulating cells (TRCs)] in vitro and in vivo. This stimulating effect is ascribed to hypoxia-induced reactive oxygen species (ROS) that activates Akt and NF-κB, dependent on the attenuated tricarboxylic acid (TCA) cycle. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 48 publications
(57 reference statements)
1
44
0
Order By: Relevance
“…Previously, CLE was examined as a tremendous source of polyphenol (Sahan et al, 2017;Sinkovič et al, 2015) and though we found a high content of gallic acid among 11 standards and Our study highly recommended to characterize the bioactive compounds in the green chicory leaf. Phenolic compounds that mostly found in plants are play roles in the prevention of oxidative damage in living organisms that perpetuated an enormous amount of chronic diseases (Graziani et al, 2005;Mijan et al, 2019;Tang et al, 2019). Furthermore, reactive oxygen species (ROS) are inevitable byproducts in physiological processes that required neutralized by antioxidants and enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, CLE was examined as a tremendous source of polyphenol (Sahan et al, 2017;Sinkovič et al, 2015) and though we found a high content of gallic acid among 11 standards and Our study highly recommended to characterize the bioactive compounds in the green chicory leaf. Phenolic compounds that mostly found in plants are play roles in the prevention of oxidative damage in living organisms that perpetuated an enormous amount of chronic diseases (Graziani et al, 2005;Mijan et al, 2019;Tang et al, 2019). Furthermore, reactive oxygen species (ROS) are inevitable byproducts in physiological processes that required neutralized by antioxidants and enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Upon suppression of autophagy, levels of glucose-6-phosphatase (G6Pase) and phosphoenolpyruvate carboxykinase (PEPCK, a protein encoded by PCK2) are reduced in the human HCC cell line HepG2 ( Jeon et al, 2015 ). Hypoxia-inducible factor 1α (HIF-1α) can promote the growth of human breast tumor-repopulating cells by downregulating PCK2 ( Tang et al, 2019 ). However, a number of studies have reported that PEPCK coordinates the regulation of central carbon metabolism to promote tumor cell growth ( Montal et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The α-KG analogue dimethyl 2-ketoglutarate allows excess succinate/fumarate to be transferred from the mitochondria to the cytoplasm, where it can impair prolyl hydroxylase and thus stabilize and activate HIF-1α, eventually leading to increased glycolysis and the acquisition of the stem-like characteristics of breast cancer cells (118). In addition, the upregulation of HIF-1α, under hypoxia, inhibits the expression of mitochondrial phosphoenolpyruvate carboxykinase, which leads to a weakened tricarboxylic acid cycle and the enrichment of fumarate, ultimately leading to increased ROS levels and breast CSC growth (123). In conclusion, HIF-1 appears to mainly act as an intermediate participant regulating the complex conversion mechanism of glycolysis and OXPHOS and the generation and maintenance of stemness in CSCs.…”
Section: Role Of Hif-1 In Metabolic Reprogramming Of Cscsmentioning
confidence: 99%